Capturing and quantifying tactical behaviors in small-sided and conditioned games in soccer: a systematic review - Coito, N.; Davids, K.; Folgado, H.; Bento, T.; Travassos, B. (Research Quarterly for Exercise and Sport, 2022)
Purpose: To systematically describe and analyze the tracking systems, the variables, and the statistical methods used to evaluate the players and teams` tactical behavior in small-sided and conditioned games (SSCGs).